AB1120 A TRIAD OF ULTRASOUND DETECTED HIGH-GRADE SYNOVITIS (MID TARSAL & ANKLE JOINTS), HIGH-GRADE TENOSYNOVITIS IN (TIBIALIS POSTERIOR & PERONEAL TENDONS) AND EROSIONS OF FIBULAR DISTAL END IS HIGHLY SUGGESTIVE OF CHARCOT ARTHROPATHY. (2nd June 2020) - Mortada, M. A.; Ezz El_din, N.; Hammad, M.
Abstract : Background: Charcot arthropathy poses many clinical challenges in its diagnosis and management. Ultrasonography (US) may be able to identify pathological changes in cases of Charcot arthropathy (1). Objectives: to characterize the ultrasonographicfeatures of patients in early pre-radiographic stages of neuropathic (Charcot) arthropathy. Methods: This is an extension of our previous study of ultrasonographic features Charcot ankle and foot (1). an observational studywhere 42 patients with neuropathic (Charcot) arthropathy of the footbetween January 2013 and october 2019 were enrolled. Inclusion criteria included: 1- Foot pain and swelling. 2- Typical MRI findings of Charcot arthropathy in the form of subcondral bone marrow edema with or without sub-chondralmicrofractures, joint effusion or soft-tissue inflammation. 3- Grade 0 Modified Eichenholtz classification system which means normal radiography of the affected foot. Patients with other forms of arthropathy that may mimic Charcot arthropathy e.g. gouty arthritis and rheumatoid arthritis, were excluded from the study.Ultrasonographic (grey scale and Doppler US) examination of mid-tarsal and ankle joints was performed according to the EULAR guidelines. Results: Synovitis and effusionatmid tarsal joints were found in all patients and to a lesser extent in the ankle joints. High degree Doppler activity at both ankle and mid tarsal joints could be observed in most patients. Bony erosions were also common as well as tendonitis. A triad of active synovitis (in mid tarsal joints and ankle joints), active tendonitis (of tibialis posterior and peroneal tendons) and erosions in the distal end of fibula was present in 40 (95.2%) cases. Conclusion: our study confirms the ability of ultrasonography to detect inflammatory lesions in early stages of Charcot arthropathy. References: [1]Mortada M, Hammad M, Ezzeldin N..Annals of the Rheumatic Diseases 2016;75:1231-1232. Disclosure of Interests: None declared